Formation of Figurative Thinking of Primary School Pupils With Teaching Methods - kizi, Nurmatova Mokhinur Erkinjon (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses the formation of figurative thinking of primary school pupils through the methods used in the educational process, the development of creative and verbal – logical thinking.